TECHNOLOGY OF ORGANIZATION OF WEBSITE OF THE INSTITUTION BASED ON THE DIVISION OF RIGHTS AND RESPONSIBILITIES OF STRUCTURAL UNITS - Vladimir E. Belchenko (Moscow Polytechnic University, 2016)
The article touches on the questions of the technology of creating the official websites of the institution based on the technology of access rights distribution. The experience of Armavir State Pedagogical Academy in using an approach to arrange site editing allowing to place large amounts of information is presented.